Effect of Severity of Liver Cirrhosis on Surgical Outcomes of Hepatocellular Carcinoma After Liver Resection and Microwave Coagulation - Li, Jiang; Tao, Hai-su; Li, Jian; Wang, Wen-qiang; Sheng, Wei-wei; Huang, Zhi-yong; Zhang, Er-lei (Frontiers in Oncology, 2021)
Background Liver resection (LR) and percutaneous microwave coagulation therapy (PMCT) are both considered as radical treatments for small hepatocellular carcinoma (HCC). However, it is still unclear whether to select LR or PMCT in HCC patients with different degrees of liver cirrhosis. The purpose of this study was to compare the efficacy of LR and PMCT in the treatment of solitary and small HCC accompanied with different degrees of liver cirrhosis. Methods In this study, 230 patients with solitary HCC lesions ≤ 3 cm and Child-Pugh A liver function were retrospectively reviewed. Among these patients, 122 patients underwent LR, and 108 received PMCT. The short- and long-term outcomes were compared between these two procedures. Severity of liver cirrhosis was evaluated by using clinical scoring system (CSS) as previously published. Subgroup analysis based on CSS was performed to evaluate the effect of severity of liver cirrhosis on surgical outcomes after LR and PMCT. Results There was no mortality within 90 days in both groups. Major complications were significantly more frequent in the LR group than in the PMCT group (18.8% vs. 4.6%, p<0.001). However, LR provided better surgical outcomes than PMCT. The 5-year overall survival (OS) rates for the LR and PMCT groups were 65.2% and 42%, respectively (p=0.006), and the corresponding disease-free survival (DFS) rates were 51.7% and 31.5%, respectively (p=0.004). Nevertheless, subgroup analysis showed that PMCT provided long-term outcomes that were similar to LR and lower surgical complications in HCC patients with CSS score≥4. Conclusions LR may provide better OS and DFS rates than PMCT for patients with solitary HCC lesions ≤ 3 cm and Child-Pugh A liver function irrespective of liver cirrhosis. PMCT should be viewed as the optimal treatment for solitary and small HCC with severe cirrhosis.